2015
DOI: 10.3906/vet-1505-28
|View full text |Cite
|
Sign up to set email alerts
|

In situ degradation of almond (Prunus dulcis L.) hulls, a potential feed material for ruminants

Abstract: IntroductionWith the dramatic rise in prices of corn, alfalfa, and other traditional feed ingredients, nutritionists are getting more creative and turning to nontraditional products (1). Agricultural residues are byproducts of cereals, sugarcane, oilseeds, oil plants, vegetables, and fruits obtained during harvesting and processing of a commodity from which human food is derived (2). These byproducts have been of interest to many researchers since the 1970s because of the desire to understand and reduce enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
3
8
0
2
Order By: Relevance
“…GAL green almond leaf, DAL dry almond leaf, GAH green almond hulls, DAH dry almond hulls of Iran. Jafari et al (2015) observed that almond hulls contain NDF and ADF contents of 300 and 220 g kg -1 DM, respectively. These results compared to those of the current study, indicates a wide difference in NDF and ADF contents even from among Iranian almond hulls only.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…GAL green almond leaf, DAL dry almond leaf, GAH green almond hulls, DAH dry almond hulls of Iran. Jafari et al (2015) observed that almond hulls contain NDF and ADF contents of 300 and 220 g kg -1 DM, respectively. These results compared to those of the current study, indicates a wide difference in NDF and ADF contents even from among Iranian almond hulls only.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The NDF content of all the experimental diets were above the critical value of 60%. According to Jafari et al (2015) and Kholif et al (2016), an NDF content in forage feeds above the critical level of 60%decreases voluntary feed intake, feed conversion efficiency and longer retention time of feeds in the gastro-intestinal truck in livestock.…”
Section: In Vivo and In Vitro Nutrient Degradability Coefficientsmentioning
confidence: 99%
“…(1995), the AH were commercial AH and therefore contained debris. Based on the lignin and fibre content, it is unlikely that the AH used in other studies (Jafari et al ., 2011, 2015; Elahi et al ., 2017) were pure AH. To the best of our knowledge, there are no reports in the literature for the in vitro fermentability of pure AH.…”
Section: Introductionmentioning
confidence: 99%